Seizure in geriatric population – An unheeded integer - Namitha Narayanan; Shivamalarvizhi Selvaraj; Abdulmuthalif Mohamedkalifa; Archana Gaur; Ariyanachi Kaliappan; Kotha Sugunakar Reddy; Jeganathan Geetha; Varatharajan Sakthivadivel (Journal of Family Medicine and Primary Care, 2023)
Background: Epilepsy is one of the most prevalent neurological conditions among the elderly. Age-related epileptogenic disorders as well as the ageing itself pose a risk for seizures in the elderly. The lack of witnesses, non-specific symptoms, and transient symptoms make the diagnosis challenging in the elderly. Aim: This study aimed to assess the various presentation and aetiology for the seizure disorder in the elderly population. Materials and Methods: A total of 125 elderly patients ≥60 years with new onset seizure were included in the study. Demographic data, co-morbidities, and clinical presentation of seizure were elicited. Hemogram, liver and renal function tests, random blood sugar, electrolytes, and serum calcium were analysed. Computed tomography (CT), magnetic resonance imaging (MRI) brain, and electroencephalogram (EEG) were performed. Results: Seizure was seen predominantly in the males with age group of 60–70 years. Generalized tonic-clonic seizure was the commonest presentation, followed by focal seizures. The leading causes of seizures were cerebral vascular accidents, metabolic conditions, and alcohol. CT brain was abnormal in 49%, and 73% of the patients showed abnormality in MRI brain. EEG was abnormal in 17.3% of patients. Temporal lobe infarction was the commonest, trailed by parieto-temporal and frontal lobe involvement. Conclusion: Seizures in the elderly have varied clinical signs and aetiology. An awareness about these atypical presentation and aetiology is essential for the early diagnosis and management to prevent morbidity.